2022
DOI: 10.3389/fnins.2022.843396
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Amygdala Histone Acetylation in Early Life Stress-Induced Visceral Hypersensitivity and Emotional Comorbidity

Abstract: Patients with irritable bowel syndrome (IBS) experience not only enhanced visceral pain but also emotional comorbidities, such as anxiety and depression. Early life stress (ELS) is a high-risk for the development of IBS. Literatures have reported an important epigenetic modulation in sustaining extrinsic phenotypes. The amygdala is closely related to the regulation of visceral functions and emotional experiences. In this study, we hypothesized that ELS-induced reprogramming inappropriate adaptation of histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…19 Additionally, Our previous study reported that neonatal CRD resulted in visceral hypersensitivity and anxiety-like behaviors in adult rats. 20 To verify whether the effect of LY3000328 on visceral pain was specific, the open-field test was performed to detect locomotor activity and anxiety-like behaviors before and after the administration of LY3000328 in IBS-like rats. Data analysis showed that LY3000328 did not affect the total distance, the average speed, the central area total distance and the central area total time of IBS-like rats (Figure 2(h)–(k)), suggesting the effect of LY3000328 on visceral pain was specific in IBS-like rats.
Figure 2.LY3000328, a selective Cat S inhibitor, attenuated visceral hypersensitivity but did not affect locomtor activity and anxiety-like behaviors in IBS-like rats.
…”
Section: Resultsmentioning
confidence: 99%
“…19 Additionally, Our previous study reported that neonatal CRD resulted in visceral hypersensitivity and anxiety-like behaviors in adult rats. 20 To verify whether the effect of LY3000328 on visceral pain was specific, the open-field test was performed to detect locomotor activity and anxiety-like behaviors before and after the administration of LY3000328 in IBS-like rats. Data analysis showed that LY3000328 did not affect the total distance, the average speed, the central area total distance and the central area total time of IBS-like rats (Figure 2(h)–(k)), suggesting the effect of LY3000328 on visceral pain was specific in IBS-like rats.
Figure 2.LY3000328, a selective Cat S inhibitor, attenuated visceral hypersensitivity but did not affect locomtor activity and anxiety-like behaviors in IBS-like rats.
…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced H3 acetylation may stimulate synaptic plasticity-related gene (PKMζ), resulting in anxiety-like behavior. 268 …”
Section: Histone Modification In Neuropsychiatric Disordersmentioning
confidence: 99%
“…The incidence of IBS is higher in first-degree blood relatives than in spouses of patients, and genetic and psychological factors can be more important than environmental factors [ 146 ]. Twin studies emphasize that genetic and psychological processes may explain familial clustering of IBS and that both heredity and social learning contribute to its aetiology [ [148] , [149] , [150] , 205 , 206 ].…”
Section: Summary With Hypothesismentioning
confidence: 99%